Pengaruh Pemberian Ekstrak Kulit Buah Alpukat (Persea Americana) Terhadap Kadar Malondialdehida (MDA) Jaringan Hepar Tikus Putih (Rattus norvegicus) Jantan Galur Wistar yang Diinduksi Parasetamol Dosis Tinggi - YUNITA SURYA PRATIWI; SULISTIANA PRABOWO (Universitas Hang Tuah, 2018)
Abstract Administration of high-dose paracetamol may increase metabolic pathways that produce N-acetyl-p-benzoquinonimine (NAPQI). NAPQI is reactive substance, resulting in hepatic tissue damage and increase liver MDA level. Avocado peel extract contains flavonoids that act as antioxidants so it is expected may decrease liver MDA level of high-dose paracetamol administration. This research used 24 male Wistar rats divided into 3 groups: group of rats fed with standard food, group of rats given paracetamol 1,750 mg/kg BW on day 8, and group of rats given avocado peel extract 1,400 mg/kg/day for 8 days and paracetamol 1750mg/kg BW on day 8. Liver MDA levels were checked on day 9 by thiobarbituric acid (TBA) method. The One-Way ANOVA test showed that the liver MDA level of the group of rats given high dose of paracetamol (x=312.38±47.830 nmol/g) was significantly higher (p = 0.001) compared to the liver MDA level of the group of rats fed with standard food (x=184.50±57.021 nmol/g). The liver MDA level of group of rats given high-dose paracetamol and avocado peel extract (x=268.50±91.834 nmol/g) did not significantly decrease (p =0.213) compared to the liver MDA level of group of rats given high dose of paracetamol (x=312.38±47.830 nmol/g). The conclusion of this research showed that high-dose paracetamol significantly increased liver MDA level and avocado peel extract tend to decrease liver MDA level because avocado peel consists flavonoid, hydroxynnamic acid, keratinoid, vitamin C, dan vitamin E that function as antioxidants.